The evidential value of carcass traces in combating stock theft in South Africa - Maluleke, Witness (Penerbit Universiti Kebangsaan Malaysia, 2022)
This qualitative exploratory study closely look at the evidential value of carcass traces in combating stock theft in South Africa. It was confined to the selected areas of KwaZulu-Natal (KZN) Province of South Africa. The Deoxyribonucleic Acid (DNA) technology, DNA testing, DNA profiling or Genetic fingerprinting refers to a technique adopted to identify and distinguish livestock by their DNA samples, focusing on patterns uniqueness of DNA sources (Carcass, fingerprints, footprints, hair, skin cells, blood, bodily fluids, pieces of clothing and fibres, alike). About 49 participants were purposively sampled, all from the KZN Province. The data was collected through Key Informant Interviews (KII) and Focus Group Discussions (FGDs). The inductive thematic methods was employed for data analysis. This study established that crime scenes involving livestock should be investigated using the same principles as any other crime scenes. It is also confirmed that every time contact is made with another person, place, or object, it results in an exchange of physical materials, carcass includes. Summarily, no matter where a stock thieve criminal go or do, by coming into contact with carcass, they can leave evidence behind, including the mentioned various DNA sources, which could positively lead to the scientific reconstruction of events, interpretation of observations and measurements from the stock theft scenes to collect physical evidence. For recommendations, the Anti-Stock theft structures should avoid mistakes in the recovering of stock theft scenes, sample collections or test procedures. They should ensure that the results are accurate by following all procedural measures, lay down guidelines for maintaining the chain of custody to ensure that the DNA tests become conclusive, and they should further provide detailed information about discovered carcass, while placing more emphasis on this type of evidence.